Corticosteroid induced avascular necrosis and COVID-19: The drug dilemma - Banerjee, Indrajit; Robinson, Jared; Sathian, Brijesh (Nepal Journal of Epidemiology, 2021)
The severe and life-threatening nature of the COVID-19 infection, the ARDS (acute respiratory distress syndrome) as well as the cytokine storm induced by the infection, commands lifesaving high doses of steroid therapy. As in all pharmacological therapies adverse effects are present. One such adverse effect which is being reported is corticosteroid induced avascular necrosis of the femoral head/ osteonecrosis of the femoral head. It must be noted that AVN principally affects the femoral head and most commonly the anterolateral aspect thereof as it is the crux of weight bearing. Corticosteroids induce fat mobilization and this thus innately enhances the likelihood of fat emboli developing from the liver to occlude minor blood vessels in the femur, this thereby compromises the microvascular environment. Superadded to this the steroid therapy disrupts calcium metabolism and homeostasis which induces hypertrophy in the intramedullary fat cells, Gaucher cells and inflammatory cells; whilst increasing the activity of osteoclasts, thus increasing bone resorption and decreasing calcium uptake and deposition; ultimately leading to an insufficiency in the trabecular and cortical bone. This insufficiency thus equates to an increased intraosseous pressure which impedes intramedullary circulation and results in avascular necrosis. It is evident that avascular necrosis is directly caused by high dose steroid therapy, however the case reports have very clearly indicated that the rapid onset of AVN post recovery from the COVID-19 infection cannot be solely attributed to steroid therapy and that another benefactor induced by the COVID-19 infection is at play. It is thus vital for treating physicians to take cognisance of this adverse effect post recovery and therefore should ensure that prophylactic bisphosphonate therapy is initiated timeously and congruently.